MAHAR PERNIKAHAN SUKU BUGIS DITINJAU DARI HUKUM ISLAM DI DESA LAPRI KECAMATAN SEBATIK KALIMANTAN UTARA - wahyudin (Program Studi Perbandingan Mazhab, Fakultas Syariah, Universitas Islam Negeri (UIN) Datokarama Palu, 2020)
This work discusses the marriage dowry of the Bugis tribe in terms of Islamic law in Lapri Village, Sebatik District, North Kalimantan. The problems to be examined in this research are, how is the position of the dowry, the process of determining the dowry of the Bugis tribe in Lapri Village, Sebatik District, North Kalimantan and how the Islamic law review regarding the marriage dowry of the Bugis tribe in Lapri Village, Sebatik District, North Kalimantan. The research method used in this research is a type of qualitative research, namely the type of research used to examine the conditions of natural objects. The results showed that the process of determining the dowry or wedding ceremony of the Bugis tribe in Lapri Village, Sebatik District was discussed at the time of ma'duta and the level or amount was decided when mappetu was present, namely, at the meeting of the two parties, both from the bride and the groom-male.